Characterization of two midgut proteinases of helicoverpa armigera and their interaction with proteinase inhibitors - Telang, M. A.; Giri, Ashok P.; Sainani, Mohini N.; Gupta, Vidya S. (Journal of Insect Physiology, 2005)
Two serine proteinases from the midgut of Helicoverpa armigera have been partially purified and characterized. One proteinase, HGP-1, was capable of hydrolyzing a synthetic substrate of elastase and was inhibited by elastatinal. The second proteinase, HGP-2, was inhibited by a trypsin inhibitor. Molecular weights of HGP-1 and HGP-2 were approximately 26.0 and 29.0 kDa, respectively. Both the proteinases exhibited alkaline pH optima in the range of 10-11. Furthermore, interaction of HGP-1 and HGP-2 with proteinase inhibitors (PIs) from host and non-host plants was studied. HGP-1 was not only insensitive to a PI from chickpea (host) but was also able to degrade it. The same PI from chickpea was able to inhibit over 50% activity of HGP-2. On the contrary, PIs from potato (non-host) showed strong inhibition of both, HGP-1 and HGP-2 and also demonstrated protection of chickpea seed proteins from digestion by both the HGPs. These results could provide important clues in designing strategies for sustainable use of plant PIs in developing insect-tolerant transgenic plants. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: elastase; Helicoverpa armigera gut proteinases; insect-resistant plants; plant proteinase inhibitors

Changes in volatile composition during fruit development and ripening of `Alphonso' mango - Pandit, Sagar S.; Kulkarni, Ram S.; Chidley, Hemangi G.; Giri, Ashok P.; Pujari, Keshav H.; Koellner, Tobias G.; Degenhardt, Joerg; Gershenzon, Jonathan; Gupta, Vidya S. (Journal of the Science of Food and Agriculture, 2009)
BACKGROUND: Volatile blends of five developing and five ripening stages of mango (Mangifera indica L. cv. Alphonso) were investigated along with those of flowers and leaves. Raw and ripe fruits of cv. Sabia were also used for comparison. RESULTS: A total of 55 volatiles belonging to various chemical classes such as aldehydes, alcohols, mono- and sesquiterpene hydrocarbons, lactones and furanones were identified. In all Alphonso tissues monoterpenes quantitatively dominated, with 57-99% contribution; in particular, (Z)-ocimene was found in the highest amount. Ripeness was characterized by the de novo appearance of lactones and furanones in the blend of monoterpenes. Sabja was distinguished by the abundance of monoterpene hydrocarbons in the raw fruit, and that of sesquiterpene hydrocarbons and their derivatives in the ripe stage. CONCLUSION: Various stages of the Alphonso fruit during transition from flower to ripe fruit are characterized by unique volatile signatures that are distinguished from each other by the qualitative and quantitative appearance of different volatile compounds. Thus volatiles can be highly informative markers while studying the development and ripening of mango. (C) 2009 Society of Chemical Industry
Keywords: Deogad; Gas chromatography; Mangifera indica; mango products; ripening indicator; Sabja

Cultivar relationships in mango based on fruit volatile profiles - Pandit, Sagar S.; Chidley, Hemangi G.; Kulkarni, Ram S.; Pujari, Keshav H.; Giri, Ashok P.; Gupta, Vidya S. (Food Chemistry, 2009)
Aroma volatiles of mango (Mangifera indica L.) determine consumer acceptability and influence selection, whilst breeding. To assess their variety, composition and possible impact on cultivar relationships, volatile blends of 22 Indian and five non-Indian cultivars were investigated using solvent extraction and gas chromatography. Totally 84 volatiles belonging to various chemical classes were detected. Based on the Cumulative Occurrence of members of these classes, cultivars were grouped as monoterpene or sesquiterpene dominant. a-Pinene, beta-myrcene and beta-caryophyllene were found in all 27 cultivars. For ordination, common compounds with high (relative) concentration provided quantitative characters, whereas the rare and lesser ones provided qualitative (binary) characters; non-Indian cultivars separated from Indian ones but displayed close relations within their groups. In conclusion, mango flavour is dominated qualitatively as well as quantitatively by terpene hydrocarbons; ancient selection of mango cultivars is hinted to be driven by different aroma characters in different parts of the world. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Flavour; GC-MS; Mangifera indica; Multivariate analysis; Ordination

Characterization of a chemostable serine alkaline protease from Periplaneta americana - Sanatan, Prashant T.; Lomate, Purushottam R.; Giri, Ashok P.; Hivrale, Vandana K. (BMC Biochemistry, 2013)
Background: Proteases are important enzymes involved in numerous essential physiological processes and hold a strong potential for industrial applications. The proteolytic activity of insects' gut is endowed by many isoforms with diverse properties and specificities. Thus, insect proteases can act as a tool in industrial processes. Results: In the present study, purification and properties of a serine alkaline protease from Periplaneta americana and its potential application as an additive in various bio-formulations are reported. The enzyme was purified near to homogeneity by using acetone precipitation and Sephadex G-100 gel filtration chromatography. Enzyme activity was increased up to 4.2 fold after gel filtration chromatography. The purified enzyme appeared as single protein-band with a molecular mass of similar to 27.8 kDa in SDS-PAGE. The optimum pH and temperature for the proteolytic activity for purified protein were found around pH 8.0 and 60 degrees C respectively. Complete inhibition of the purified enzyme by phenylmethylsulfonyl fluoride confirmed that the protease was of serine-type. The purified enzyme revealed high stability and compatibility towards detergents, oxidizing, reducing, and bleaching agents. In addition, enzyme also showed stability towards organic solvents and commercial detergents. Conclusion: Several important properties of a serine protease from P. Americana were revealed. Moreover, insects can serve as excellent and alternative source of industrially important proteases with unique properties, which can be utilized as additives in detergents, stain removers and other bio-formulations. Properties of the P. americana protease accounted in the present investigation can be exploited further in various industrial processes. As an industrial prospective, identification of enzymes with varying essential properties from different insect species might be good approach and bioresource.
Keywords: Chemostability; Industrial catalyst; Insect proteases; Periplaneta americana; Serine alkaline protease

Characterization of three novel isoprenyl diphosphate synthases from the terpenoid rich mango fruit - Kulkarni, Ram; Pandit, Sagar; Chidley, Hemangi G.; Nagel, Raimund; Schmidt, Axel; Gershenzon, Jonathan; Pujari, Keshav; Giri, Ashok P.; Gupta, Vidya (Plant Physiology and Biochemistry, 2013)
Mango (cv. Alphonso) is popular due to its highly attractive, terpenoid-rich flavor. Although Alphonso is clonally propagated, its fruit-flavor composition varies when plants are grown in different geo-climatic zones. Isoprenyl diphosphate synthases catalyze important branch-point reactions in terpenoid biosynthesis, providing precursors for common terpenoids such as volatile terpenes, sterols and carotenoids. Two geranyl diphosphate synthases and a farnesyl diphosphate synthase were isolated from Alphonso fruits, cloned for recombinant expression and found to produce the respective products. Although, one of the geranyl diphosphate synthases showed high sequence similarity to the geranylgeranyl diphosphate synthases, it did not exhibit geranylgeranyl diphosphate synthesizing activity. When modeled, this geranyl diphosphate synthase and farnesyl diphosphate synthase structures were found to be homologous with the reference structures, having all the catalytic side chains appropriately oriented. The optimum temperature for both the geranyl diphosphate synthases was 40 degrees C and that for farnesyl diphosphate synthase was 25 degrees C. This finding correlated well with the dominance of monoterpenes in comparison to sesquiterpenes in the fruits of Alphonso mango in which the mesocarp temperature is higher during ripening than development. The absence of activity of these enzymes with the divalent metal ion other than Mg2+ indicated their adaptation to the Mg2+ rich mesocarp. The typical expression pattern of these genes through the ripening stages of fruits from different cultivation localities depicting the highest transcript levels of these genes in the stage preceding the maximum terpene accumulation indicated the involvement of these genes in the biosynthesis of volatile terpenes. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: Alphonso; Flavor variation; Fruit; Isoprenyl diphosphate synthase; Mangifera indica; Terpene volatiles

Complementation of intramolecular interactions for structural-functional stability of plant serine proteinase inhibitors - Joshi, Rakesh S.; Mishra, Manasi; Suresh, C. G.; Gupta, Vidya S.; Giri, Ashok P. (Biochimica Et Biophysica Acta-General Subjects, 2013)
Background: Plant protease inhibitors (PIs) constitute a diverse group of proteins capable of inhibiting proteases. Among Pls, serine Pls (SPIs) display stability and conformational restrictions of the reactive site loop by virtue of their compact size, and by the presence of disulfide bonds, hydrogen bonds, and other weak interactions. Scope of review: The significance of various intramolecular interactions contributing to protein folding mechanism and their role in overall stability and activity of SPIs is discussed here. Furthermore, we have reviewed the effect of variation or manipulation of these interactions on the activity/stability of SPIs. Major conclusions: The selective gain or loss of disulfide bond(s) in SPIs can be associated with their functional differentiation, which is likely to be compensated by non-covalent interactions (hydrogen bonding or electrostatic interactions). Thus, these intramolecular interactions are collectively responsible for the functional activity of SPIs, through the maintenance of scaffold framework, conformational rigidity and shape complementarities of reactive site loop. General significance: Structural insight of these interactions will provide an in-depth understanding of kinetic and thermodynamic parameters involved in the folding and stability mechanisms of SPIs. These features can be explored for engineering canonical SPIs for optimizing their overall stability and functionality for various applications. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Disulfide bond; hydrogen bonding; Intramolecular weak interaction; Protease; Reactive site loop; Serine proteinase inhibitor

Cathepsins of lepidopteran insects: aspects and prospects - Saikhedkar, Nidhi; Summanwar, Aarohi; Joshi, Rakesh S.; Giri, Ashok P. (Insect Biochemistry and Molecular Biology, 2015)
Molecular understanding of lepidopteran physiology has revealed that proteases consist of one of the central regulatory/reacting system for insect growth and survival. Among the various proteases, cathepsins are the most crucial cellular proteases, which play vital roles during insect development. In the present review, we have discussed various aspects of the lepidopteran insect cathepsins, emphasizing their roles in processes like development, growth, metamorphosis, apoptosis and immunity. Cathepsins are categorized into different types on the basis of their sequence diversification, leading to variation in structure and catalytic function. Cathepsins exhibit tissue and stage specific expression pattern which is fine-tuned by a delicate balance of expression, compartmentalization, zymogen activation, inhibition by protein inhibitors and degradation. The indispensability of cathepsins as cellular proteases in the above mentioned processes proposes them as novel targets for designing effective and specific insect controlling strategies. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Apoptosis; Cathepsin; Cysteine/aspartate protease; Development; Lepidoptera; Pest control; Stress response

Characterization of roseomonas and nocardioides spp. for arsenic transformation - Bagade, Aditi V.; Bachate, Sachin P.; Dholakia, Bhushan B.; Giri, Ashok P.; Kodam, Kisan M. (Journal of Hazardous Materials, 2016)
The metalloid arsenic predominantly exists in the arsenite [As(III)] and arsenate [As(V)]. These two forms are respectively oxidized and reduced by microbial redox processes. This study was designed to bioprospect arsenic tolerating bacteria from Lonar lake and to characterize their arsenic redoxing ability. Screening of sixty-nine bacterial species isolated from Lonar lake led to identification of three arsenic oxidizing and seven arsenic-reducing species. Arsenite oxidizing isolate Roseomonas sp. L-159a being closely related to Roseomonas cervicalis ATCC 49957 oxidized 2 mM As(III) in 60 h. Gene expression of large and small subunits of arsenite oxidase respectively showed 15- and 17-fold higher expression. Another isolate Nocardioides sp. L-37a formed a clade with Nocardioides ghangwensis JC2055, exhibited normal growth with different carbon sources and pH ranges. It reduced 2 mM As(V) in 36 h and showed constitutive expression of arsenate reductase which increased over 4-fold upon As(V) exposure. Genetic markers related to arsenic transformation were identified and characterized from the two isolates. Moderate resistance against the arsenicals was exhibited by the two isolates in the range of 1-5 mM for As(III) and 1-200 mM for As(V). Altogether we provide multiple evidences to indicate that Roseomonas sp. and Nocardioides sp. exhibited arsenic transformation ability. (C) 2016 Elsevier B.V. All rights reserved.

Characterization of two coleopteran alpha-amylases and molecular insights into their differential inhibition by synthetic alpha-amylase inhibitor, acarbose - Channale, Sonal M.; Bhide, Amey J.; Yadav, Yashpal; Kashyap, Garima; Pawar, Pankaj K.; Maheshwari, V. L.; Ramasamy, Sureshkumar; Giri, Ashok P. (Insect Biochemistry and Molecular Biology, 2016)
Post-harvest insect infestation of stored grains makes them unfit for human consumption and leads to severe economic loss. Here, we report functional and structural characterization of two coleopteran alpha-amylases viz. Callosobruchus chinensis alpha-amylase (CcAmy) and Tribolium castaneum alpha-amylase (TcAmy) along with their interactions with proteinaceous and non-proteinaceous alpha-amylase inhibitors. Secondary structural alignment of CcAmy and TcAmy with other coleopteran alpha-amylases revealed conserved motifs, active sites, di-sulfide bonds and two point mutations at spatially conserved substrate or inhibitor binding sites. Homology modeling and molecular docking showed structural differences between these two enzymes. Both the enzymes had similar optimum pH values but differed in their optimum temperature. Overall, pattern of enzyme stabilities were similar under various temperature and pH conditions. Further, CcAmy and TcAmy differed in their substrate affinity and catalytic efficiency towards starch and amylopectin. HPLC analysis detected common amylolytic products like maltose and maltotriose while glucose and malto-tetrose were unique in CcAmy and TcAmy catalyzed reactions respectively. At very low concentrations, wheat alpha-amylase inhibitor was found to be superior over the acarbose as far as complete inhibition of amylolytic activities of CcAmy and TcAmy was concerned. Mechanism underlying differential amylolytic reaction inhibition by acarbose was discussed. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Acarbose; alpha-amylase; alpha-amylase inhibitor; Callosobruchus chinensis; Coleoptera; Tribolium castaneum

Comparative functional characterization of eugenol synthase from four different ocimum species: implications on eugenol accumulation - Anand, Atul; Jayaramaiah, Ramesha H.; Beedkar, Supriya D.; Singh, Priyanka A.; Joshi, Rakesh S.; Mulani, Fayaj A.; Dholakia, Bhushan B.; Punekar, Sachin A.; Gade, Wasudeo N.; Thulasiram, Hirekodathakallu V.; Giri, Ashok P. (Biochimica Et Biophysica Acta-Proteins and Proteomics, 2016)
Isoprenoids and phenylpropanoids are the major secondary metabolite constituents in Ocimum genus. Though enzymes from phenylpropanoid pathway have been characterized from few plants, limited information exists on how they modulate levels of secondary metabolites. Here, we performed phenylpropanoid profiling in different tissues from five Ocimum species, which revealed significant variations in secondary metabolites including eugenol, eugenol methyl ether, estragole and methyl cinnamate levels. Expression analysis of eugenol synthase (EGS) gene showed higher transcript levels especially in young leaves and inflorescence; and were positively correlated with eugenol contents. Additionally, transcript levels of coniferyl alcohol acyl transferase, a key enzyme diverting pool of substrate to phenylpropanoids, were in accordance with their abundance in respective species. In particular, eugenol methyl transferase expression positively correlated with higher levels of eugenol methyl ether in Ocimum tenuiflorum. Further, EGSs were functionally characterized from four Ocimum species varying in their eugenol contents. Kinetic and expression analyses indicated, higher enzyme turnover and transcripts levels, in species accumulating more eugenol. Moreover, biochemical and bioinformatics studies demonstrated that coniferyl acetate was the preferred substrate over coumaryl acetate when used, individually or together, in the enzyme assay. Overall, this study revealed the preliminary evidence for varied accumulation of eugenol and its abundance over chavicol in these Ocimum species. Current findings could potentially provide novel insights for metabolic modulations in medicinal and aromatic plants. (C) 2016 Elsevier B.V. All rights reserved.

Combinatorial approach through in vitro regeneration and phytochemical profiling of ceropegia media (huber) ans.: a potential way forward in the conservation of an endangered medicinal plant from the western ghats in India - Pandey, Meena; Dholakia, Bhushan B.; Jayaramaiah, Ramesha H.; Punekar, Sachin A.; Giri, Ashok P. (Journal of Plant Growth Regulation, 2020)
Ceropegia mediais an endemic and endangered plant as its propagation through seeds is unreliable due to low germination, slow growth and seedling decay under natural conditions. Also, tubers of this plant are edible serving as carbohydrate source with medicinal values leading to severe population decline in the natural habitat. To provide a sustainable solution, an efficient in vitro propagation protocol along with phytochemical profiling was developed forC. media. Callus cultures were induced from seedling and wild leaf tissues using the most effective Murashige and Skoog's (MS) medium with 2,4-dichlorophenoxyacetic acid (2,4-D; 2 mu M) and sucrose (3%). Somatic embryos were acquired on MS medium with 1 mu M 6-Benzylaminopurine (BAP) and 1 mu M 2,4-D. Conversion into plantlets was attained only from tissue culture-derived seedling leaf (TCDSL) explant. Further, in vitro tuberization was achieved from TCDSL callus with BAP and Naphthalene acetic acid (NAA). AgNO(3)as an elicitor had a positive effect on both fresh and dry weights of callus. Successful acclimatization (58%) was attained after two months resulting in normal phenotype in pots. Further, metabolite profiles of ten different tissues from wild and in vitro plants were compared. Total 82 compounds comprising alkaloids, fatty acids, fatty acid ester, steroids, terpenes and hydrocarbons were identified. Overall, results suggested enhanced production of selected metabolites with in vitro propagation and AgNO3, alleviating the problem of unavailability of planting materials. Thus, the current study might offer potential ways for the conservation of such RED enlisted species asC. media. [GRAHICS]
Keywords: Ceropegia media; GC-MS; Microtuberization; Secondary metabolites; Silver nitrate; somatic embryogenesis

Characterized constituents of insect herbivore oral secretions and their influence on the regulation of plant defenses - Kallure, Gopal S.; Kumari, Archana; Shinde, Balkrishna A.; Giri, Ashok P. (Phytochemistry, 2022)
For more than 350 million years, there have been ongoing dynamic interactions between plants and insects. In several cases, insects cause-specific feeding damage with ensuing herbivore-associated molecular patterns that invoke characteristic defense responses. During feeding on plant tissue, insects release oral secretions (OSs) containing a repertoire of molecules affecting plant defense (effectors). Some of these OS components might elicit a defense response to combat insect attacks (elicitors), while some might curb the plant defenses (suppressors). Few reports suggest that the synthesis and function of OS components might depend on the host plant and associated microorganisms. We review these intricate plant-insect interactions, during which there is a continuous exchange of molecules between plants and feeding insects along with the associated microorganisms. We further provide a list of commonly identified inducible plant produced defensive molecules released upon insect attack as well as in response to OS treatments of the plants. Thus, we describe how plants specialized and defense-related metabolism is modulated at innumerable phases by OS during plant-insect interactions. A molecular understanding of these complex interactions will provide a means to design eco-friendly crop protection strategies.
Keywords: Effector; Elicitor; Herbivore insects; Oral secretion; Plant defense; Suppressor

Comprehensive tissue specific analysis of antioxidant potential and metabolite profiling of a vulnerable therapeutic herb Ceropegia sahyadrica - Pandey, Meena; Dholakia, Bhushan B.; Saraf, Purva S.; Punekar, Sachin A.; Giri, Ashok P. (3 Biotech, 2025)
This study investigated tissue-culture of an endangered medicinal herb, Ceropegia sahyadrica, along with tissue-specific variation in antioxidant activity and GC-MS based phytochemical profiling using wild and in vitro explants. In vitro leaf explants exhibited callus induction rate of 100% in Murashige and Skoog media containing 6-benzylaminopurine (4 mu M) and 2,4-dichlorophenoxyacetic acid (2 mu M) with 5% sucrose, whereas in vitro root explant achieved 66.7% with the combination of 2 mu M 6-benzylaminopurine and 1 mu M 2,4-dichlorophenoxyacetic acid in Murashige and Skoog medium. Microtuberization was most pronounced in in vitro root explants with a maximum response of 73.3% in 1 mu M indole-3-acetic acid, 2 mu M 6-benzylaminopurine and 5% sucrose. Scanning electron microscopy imaging revealed distinct cellular organization among tissues. Further, antioxidant potential assessed through 1,1-diphenyl-2-picrylhydrazyl radical scavenging assays and estimated total phenolic content showed metabolic variation and commonality between in vitro and wild tissues. Additionally, phytochemical profiling by gas chromatography-mass spectrometry identified 201 compounds, including alkaloids, fatty acid methyl esters, flavonoids, phytosterols and other bioactive molecules with alterations in metabolite profiles between in vitro and wild tissues. These findings demonstrated that explant origin and culture condition might significantly influence metabolic responses for conservation and ensures a reliable source of bioactive compound.
Keywords: Ceropegia- Conservation; Endemic medicinal herb; GC-MS; Metabolite profiling; Tuberization